HUBUNGAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR RANCANGAN ANGGARAN BIAYA SISWA KELAS II JURUSAN TEKNIK BANGUNAN SMK N 1 PADANG - 269-277 , Akhyar Jamil Nurman (Universitas Negeri Padang, 2014)
ABSTRACT The research is motivated were less of class II student learning outcomes Teknik Bangunan of SMK N 1 Padang subjects Real Cost Estimate. Theresearch aims was to determine whether there is a correlationbetween the learning outcomesofReal Cost Estimate of learning motivation ofReal Cost Estimate of student of II Teknik Bangunan of SMK Negeri 1 Padang . This research is a descriptive correlational study . The population subject were all students of class II Teknik Bangunan during 2012/2013 periodeis 89 students , because the population is less than 100 then the samples were taken of all members is called total sampling population totaling 89 students. The variables in research were motivated to learn as the independent variable ( X ) and the Real Cost Estimate learning outcomes as the dependent variable ( Y ). Based on the analysis of correlation r value of 0.793 obtained in the strong category and test the significance of correlations obtained tcount 7.930 > 1.988 t table then Ho is rejected. Thus it can be stated that There is a relationship between learning motivation and learning outcomes Real Cost Estimate students of II Teknik Bangunan of SMK Negeri 1 Padang, the meaning that higher learning motivation students the results of the learning outcomes Real Cost Estimate has increased. Keyword: Correlation, Learning Motivation, Learning Outcomes.